Innovative financing for city infrastructure investment by increasing the rate of return from spillover tax revenues - Naoyuki Yoshino; Nella Hendriyetty; Saloni Lakhia; Widya Alwarritzi (Asian Development Bank Institute (ADBI), 2019)
The growing trend of urban city development requires various infrastructure investments, including water supply, electricity, sanitation, transportation, and other supporting facilities. In facing this challenge, many Asian countries experience significant constraints, particularly on the issues of land acquisition and insufficient financial supply, which potentially create a time delay in infrastructure investment and huge budget deficits. If these infrastructure investments were financed by overseas investors, future exchange rate risks would have to be carried by infrastructure companies. This paper examines further ways to attract more investment in infrastructure by applying spillover tax revenues. Case studies of some innovative financing aspects of Japan and other countries are also presented.
Keywords: C31; H21; O18; R51; 330; infrastructure financing; spill-over effects; tax revenue; land acquisition; smart city; connectivity